Analisis Kinerja Mengajar Guru Perbantuan Sementara (GPS) Biologi SLTP dan SMU Se-Provinsi Nanggroe Aceh Darussalam - Hafnati Rahmatan (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
The purpose of this research is to investigate the performance of contracting Biology teachers working on preparing teaching plan and teaching learning process. The population was 54 contracting Biology teachers who were teaching at SLTP and SMU in Nanggroe Aceh Darusssalam province. The sample taken by purposive random sampling was 24 teachers. The instruments used in this study were an essay test which was used for measuring the performance of teaching plan and teaching learning process by IPKM-1 and IPKM-2. The analyzed data showed that the contracting Biology teachers’ working on making teaching plan and t teaching learning process stay at level “enough and good”. It is supported by the average score 2.53 for making teaching plan and 2.14 for teaching learning process.